An Evolutionary Link between Natural Transformation and CRISPR Adaptive Immunity - Peter Jorth (American Society for Microbiology, 2012)
ABSTRACT Natural transformation by competent bacteria is a primary means of horizontal gene transfer; however, evidence that competence drives bacterial diversity and evolution has remained elusive. To test this theory, we used a retrospective comparative genomic approach to analyze the evolutionary history of Aggregatibacter actinomycetemcomitans, a bacterial species with both competent and noncompetent sister strains. Through comparative genomic analyses, we reveal that competence is evolutionarily linked to genomic diversity and speciation. Competence loss occurs frequently during evolution and is followed by the loss of clustered regularly interspaced short palindromic repeats (CRISPRs), bacterial adaptive immune systems that protect against parasitic DNA. Relative to noncompetent strains, competent bacteria have larger genomes containing multiple rearrangements. In contrast, noncompetent bacterial genomes are extremely stable but paradoxically susceptible to infective DNA elements, which contribute to noncompetent strain genetic diversity. Moreover, incomplete noncompetent strain CRISPR immune systems are enriched for self-targeting elements, which suggests that the CRISPRs have been co-opted for bacterial gene regulation, similar to eukaryotic microRNAs derived from the antiviral RNA interference pathway. IMPORTANCE The human microbiome is rich with thousands of diverse bacterial species. One mechanism driving this diversity is horizontal gene transfer by natural transformation, whereby naturally competent bacteria take up environmental DNA and incorporate new genes into their genomes. Competence is theorized to accelerate evolution; however, attempts to test this theory have proved difficult. Through genetic analyses of the human periodontal pathogen Aggregatibacter actinomycetemcomitans, we have discovered an evolutionary connection between competence systems promoting gene acquisition and CRISPRs (clustered regularly interspaced short palindromic repeats), adaptive immune systems that protect bacteria against genetic parasites. We show that competent A. actinomycetemcomitans strains have numerous redundant CRISPR immune systems, while noncompetent bacteria have lost their CRISPR immune systems because of inactivating mutations. Together, the evolutionary data linking the evolution of competence and CRISPRs reveals unique mechanisms promoting genetic heterogeneity and the rise of new bacterial species, providing insight into complex mechanisms underlying bacterial diversity in the human body.